Comparison of some coordinative abilities in terms of team and individual sports - Peker, A. T.; Vural, M. (Journal of Education and Training Studies, 2019)
The purpose of this research is to compare some coordinative abilities in terms of team and individual sports. A total of 112 athletes were included in the research, of which 60 athletes were from individual sports (Athletics=20, Archery=20, Karate=20) with mean age of 15.02±0.813 years, mean body height of 1.64±0.88 meters and mean body weight of 54.80±11.196 kilograms and 52 athletes were from team sports (Football Player=32, Basketball Player=20) with mean age of 14.98±0.727 years, mean body height of 1.67±0.90 meters and mean body weight of 58.10±9.770 kilograms. Numbered medicine ball run test, backward medicine ball throw test and sprint at the given rhythm test were used to evaluate performances related to coordinative abilities. When our results are examined, it is seen that averages of the participants in team sports category in terms of rhythm, orientation and differentiation abilities are at better level than averages of the participants in individual sports category. It has been seen that individuals in team sports category have significantly better performance than athletes in individual sports in terms of their orientation and differentiation abilities. On the other hand, no significant difference was found for rhythm ability. Consequently, results of the study confirm our pre-research expectations. On the other hand, when literature is examined, it is significant that results obtained from other studies examining coordinative abilities of the athletes in individual sports and team sports categories are similar to our results. It has been seen in the studies in the literature that some results are not similar. It can be thought that different results are caused by age differences and differences in types and branches of sports in which athletes participate.